(3GdeYJHQ aj GdMceIs - (3gHI Gddg Hf Ydj Hf edcG GdHdOj, CHh GdHQcGJ,J (B560 (3g` s
(3ChdgG (B:s
(3GdaUd GdChd (B[ (3cdGe cdi ai JYdje GdYdhe hJYdegG(B] s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B74s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B7 - (3U (B235 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1731s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3222) s
Keywords: (3GdadSaI hGdefWbs